-12y-67=-13

Combine y and 12.

-y2-67=-13

Add 67 to both sides of the equation.

-y2=-13+67

To write -13 as a fraction with a common denominator, multiply by 77.

-y2=-13⋅77+67

To write 67 as a fraction with a common denominator, multiply by 33.

-y2=-13⋅77+67⋅33

Write each expression with a common denominator of 21, by multiplying each by an appropriate factor of 1.

Multiply 13 and 77.

-y2=-73⋅7+67⋅33

Multiply 3 by 7.

-y2=-721+67⋅33

Multiply 67 and 33.

-y2=-721+6⋅37⋅3

Multiply 7 by 3.

-y2=-721+6⋅321

-y2=-721+6⋅321

Combine the numerators over the common denominator.

-y2=-7+6⋅321

Simplify the numerator.

Multiply 6 by 3.

-y2=-7+1821

Add -7 and 18.

-y2=1121

-y2=1121

-y2=1121

Multiply both sides of the equation by -2.

-2⋅(-y2)=-2⋅1121

Simplify -2⋅(-y2).

Cancel the common factor of 2.

Move the leading negative in -y2 into the numerator.

-2⋅-y2=-2⋅1121

Factor 2 out of -2.

2(-1)⋅-y2=-2⋅1121

Cancel the common factor.

2⋅-1⋅-y2=-2⋅1121

Rewrite the expression.

-1⋅(-y)=-2⋅1121

-1⋅(-y)=-2⋅1121

Multiply.

Multiply -1 by -1.

1⋅y=-2⋅1121

Multiply y by 1.

y=-2⋅1121

y=-2⋅1121

y=-2⋅1121

Simplify -2⋅1121.

Multiply -2(1121).

Combine -2 and 1121.

y=-2⋅1121

Multiply -2 by 11.

y=-2221

y=-2221

Move the negative in front of the fraction.

y=-2221

y=-2221

y=-2221

The result can be shown in multiple forms.

Exact Form:

y=-2221

Decimal Form:

y=-1.047619‾

Mixed Number Form:

y=-1121

Solve for y -1/2y-6/7=-1/3